Postmigrant Counterpublics - Kosnick, Kira (transcript Verlag, 2026)
Can we move beyond the politics of community when it comes to understanding minoritized life in postmigrant, sexually diverse societies marked by racism? In a set of interconnected essays, Kira Kosnick explores the conflicting dynamics of community and subcultural socialities in racialized and sexually dissident urban contexts in Germany. Drawing on many years of ethnographic fieldwork, she examines how dominant framings of community turn into a burden of representation for minoritized groups. Against such framings, urban nightlife and queer, postmigrant club scenes are shown to work as counterpublics that offer spaces for dissident articulations of sexuality and postmigrant identities.